Influence of concentration and type of microcrystalline cellulose on the physical properties of tablets containing Cornelian cherry fruits - Franc Aleš; Kurhajec Slavomir; Pavloková Sylvie; Sabadková Dana; Muselík Jan (Acta Pharmaceutica)
The aim of this study was to find the optimal tablet composition with maximum content of dried fruits (Cornus mas L.). The effect of three different concentrations (12.5, 25 and 50 %) of two types of microcrystalline cellulose (Avicel® PH 101 and Avicel® PH 200) and three different compression pressures (20, 60 and 100 MPa) on the physical properties of tablet blends and tablets was studied. Tablets containing 50 % Avicel® PH 101 compressed under 100 MPa were found to have the best physical properties. This combination of composition and compression pressure resulted in stable tablets even after storage under accelerated stability conditions (6 months, 40 °C and 75 % RH).